2009
DOI: 10.1590/s1517-86922009000600010
|View full text |Cite
|
Sign up to set email alerts
|

Máxima fase estável de lactato sanguíneo e potência crítica em ciclistas bem treinados

Abstract: RESUMoO principal objetivo deste estudo foi comparar a intensidade correspondente à máxima fase estável de lactato (MLSS) e a potência crítica (PC) durante o ciclismo em indivíduos bem treinados. Seis ciclistas do sexo masculino (25,5 ± 4,4 anos, 68,8 ± 3,0kg, 173,0 ± 4,0cm) realizaram em diferentes dias os seguintes testes: exercício incremental até a exaustão para a determinação do pico de consumo de oxigênio (VO 2 pico) e sua respectiva intensidade (IVO 2 pico); cinco a sete testes de carga constante para … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 20 publications
(32 reference statements)
1
3
0
1
Order By: Relevance
“…AT1 was not significantly different from MLSS and there was a moderately significant correlation between the variables (r = 0.68). This result is in agreement with previous studies carried out with endurance runners 5,12 , cyclists 4,[13][14][15][16] , team sports 18 , physically active individuals 19 and untrained individuals 4 . Jones and Doust 12 showed that endurance runners' AT1 and MLSS were significantly similar and highly correlated (r = 0.93).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…AT1 was not significantly different from MLSS and there was a moderately significant correlation between the variables (r = 0.68). This result is in agreement with previous studies carried out with endurance runners 5,12 , cyclists 4,[13][14][15][16] , team sports 18 , physically active individuals 19 and untrained individuals 4 . Jones and Doust 12 showed that endurance runners' AT1 and MLSS were significantly similar and highly correlated (r = 0.93).…”
Section: Discussionsupporting
confidence: 93%
“…Studies with exercises on stationary bicycles for both trained cyclists and untrained individuals showed that the intensity that corresponded to the AT and the fixed [La] of 3.5 mmol.L -1 was not different from the MLSS 4,[13][14][15] . Though the AT for the fixed [La] was similar to MLSS, other studies with running 5,12,18,19 and cycling 4,[13][14][15][16] , and others with different exercise modalities, have shown a difference between the two variables 11,17,19 . The main criticism in relation to the use of this method is that it does not evaluate the individual kinetics of the lactate curve during an incremental test.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…From the 36 studies, 31 were peer reviewed (26,28,34,37–39,47,48,61,70,71,78,83,85,86,90,91,98,102–104,107,109,110,112,117,119,120,123–125) and 5 were “gray literature” including 1 conference abstract (45) and 4 thesis or dissertations or monographs (15,32,64,121). Studies' main characteristics regarding MLSS and CP testing protocols and the observed study-level effect sizes (trueμ^CPMLSS and trueσ^CPMLSS) are shown in Table 2.…”
Section: Resultsmentioning
confidence: 99%
“…Isso porque reserva o recurso do modelo matemático ao tratamento da resposta principal da cinética do VO 2 , destacando-a da reposta subsequente. Assim, possibilita a detecção do início e amplitude do CL pela observação pontual do eixo do tempo e comparação do volume de O 2 ao final do exercício 5,34,35 . Quadro 1.…”
Section: Fatores Que Interferem No CLunclassified